Elastohydrodynamic analysis of a journal bearing with different grade oils considering thermal and cavitation effects using CFD-FSI - Zainab Kadhim; Lekaa Hammed; Fatima Rahima; Ali Ridha (Diagnostyka, 2023)
This paper investigates a three-dimensional CFD analysis of hydrodynamic journal bearing performance for two different available types of lubricants, SEA 10W50 and SEA 15W40, considering thermal, elastic deformation, and cavitation effects. 3-dimensional CFD model founded on continuity, momentum, energy, in addition elasticity equations has been implemented. The analysis is performed for a bearing with different journal speeds (1000-3000rpm) and eccentricity ratios (0.1-0.9). The cavitation effect was considered using the model of Zwart–Gerber–Balamri multiphase flow model. The bearing material elastic deformation was considered by implementing the two-way FSI technique through ANSYS-FLUENT 2019 R2. A comparative study of the oil film temperature, thermal pressure, also the load capacity by the bearing has been performed. By comparing the current work's oil film temperature results with those obtained by Ferron et al (1983), with a maximum deviation between the results not exceeding 3 percent, the mathematical model was validated. The findings demonstrate that, once the cavitation consequence is taken into account, the lubricant film pressure decreases. Furthermore, at what time the bearing rotates at greater eccentricity ratios and rotational speeds, more deformation material of the bearing is seen. The current research may help in predicting the bearing performance parameters in real-world situations